Rematching Spatial Home Based School Pattern for West Jakarta - Maulia, Nisa; Koestoer, Raldi H; Saraswati, Ratna (KnE Social Sciences, 2019)
Rematching spatial home-based school pattern by using the trip distribution model is a fundamental tool in demographic related to the transport planning process of urban and interurban areas. Thus the study highlights student origin-destination movement in West Jakarta as to check the level of effectiveness of Jakarta Local Government Home Based School Regulation. School profile as secondary data was included to define two leading schools from 17 public senior high schools located in West Jakarta. Geocoordinate points of students’ addresses as primary data was collected to figure spatial Home Based School pattern. The data analysis was carried out using mapping network analysis and cross tabulation. Network Analysis was performed to set the origin-destination (OD) matrix. Cross-tabulation was applied to evaluate the frequency of home-based school travel pattern. The analysis showed that the local government regulation less worked ideally due to some constraint of trip distribution e.g. threshold and preference at two core schools of West Jakarta.